Spatial and dose–response analysis of fibrotic lung changes after stereotactic body radiation therapy. Issue 8 (23rd July 2013) - Vinogradskiy, Yevegeniy; Diot, Quentin; Kavanagh, Brian; Schefter, Tracey; Gaspar, Laurie; Miften, Moyed
Abstract : Purpose: : Stereotactic body radiation therapy (SBRT) is becoming the standard of care for early stage nonoperable lung cancers. Accurate dose–response modeling is challenging for SBRT because of the decreased number of clinical toxicity events. As a surrogate for a clinical toxicity endpoint, studies have proposed to use radiographic changes in follow up computed tomography (CT) scans to evaluate lung SBRT normal tissue effects. The purpose of the current study was to use local fibrotic lung regions to spatially and dosimetrically evaluate lung changes in patients that underwent SBRT. Methods: : Forty seven SBRT patients treated at our institution from 2003 to 2009 were used for the current study. Our patient cohort had a total of 148 follow up CT scans ranging from 3 to 48 months post‐therapy. Post‐treatment scans were binned into intervals of 3, 6, 12, 18, 24, 30, and 36 months after the completion of treatment. Deformable image registration was used to align the follow up CT scans with the pretreatment CT and dose distribution. Areas of visible fibrotic changes were contoured. The centroid of each gross tumor volume (GTV) and contoured fibrosis volume was calculated and the fibrosis volume location and movement (magnitude and direction) relative to the GTV and 30 Gy isodose centroid were analyzed. To perform a dose–response analysis, each voxel in the fibrosis volume was sorted into 10 Gy dose bins and the average CT number value for each dose bin was calculated. Dose–response curves were generated by plotting the CT number as a function of dose bin and time posttherapy. Results: : Both fibrosis and GTV centroids were concentrated in the upper third of the lung. The average radial movement of fibrosis centroids relative to the GTV centroids was 2.6 cm with movement greater than 5 cm occurring in 11% of patients. Evaluating dose–response curves revealed an overall trend of increasing CT number as a function of dose. The authors observed a CT number plateau at doses ranging from 30 to 50 Gy for the 3, 6, and 12 months posttherapy time points. There was no evident plateau for the dose–response curves generated using data from the 18, 24, 30, and 36 months posttherapy time points. Conclusions: : Regions of local fibrotic lung changes in patients that underwent SBRT were evaluated spatially and dosimetrically. The authors found that the average fibrosis movement was 2.6 cm with movement greater than 5 cm possible. Evaluating dose–response curves revealed an overall trend of increasing CT number as a function of dose. Furthermore, our dose–response data also suggest that one of the possible explanations of the CT number plateau effect may be the time posttherapy of the acquired data. Understanding normal tissue dose–response is important for reducing toxicity after SBRT, especially in cases where larger tumors are treated. The methods presented in the current work build on prior quantitative studies and further enhance the understanding of normal lung dose–response after SBRT.